Improved visible-light photoactivities of porous LaFeO3 by coupling with nanosized alkaline earth metal oxides and mechanism insight. Issue 12 (23rd May 2019) - Khan, Iltaf; Sun, Ning; Zhang, Ziqing; Li, Zhijun; Humayun, Muhammad; Ali, Sharafat; Qu, Yang; Jing, Liqiang
Abstract : It is significant to improve visible-light photoactivities of porous LaFeO3 by coupling with nanosized alkaline earth metal oxides as dual-functional platform for accepting the high level electrons and activating CO2 . Abstract : It is of significance to simultaneously enhance the charge separation and promote the surface reactant activation in photocatalysis. To this end, nanosized SrO coupled porous LaFeO3 (PLFO) nanocomposites have been successfully prepared via a one-pot carbon-sphere-hard-template (CSHT) method. Compared with bare PLFO, the as-prepared optimized nanocomposite exhibits high visible-light photoactivities as shown by over 6-fold and 1.8-fold enhancement for CO2 conversion and for 2, 4-dichlorophenol (2, 4-DCP) degradation, respectively. Based on the surface photovoltage spectra (SPS), fluorescence spectra (FS) related to the produced ˙OH amount, and temperature programmed desorption (TPD) and electrochemical reduction curves, it is demonstrated that the exceptional visible-light photoactivities are mainly attributed to the large surface area due to the porous structure, and the introduced nanosized SrO which acts not only as a platform to accept high level energy electrons (HLEEs) to enhance the charge separation but also as an activator to adsorb and catalyze CO2 (O2 ) to promote the surface chemical reactions. Additionally, this efficient strategy is versatile for other alkaline earth metal oxides, such as MgO, CaO and BaO. In comparison with the different alkaline earth metal oxide modifications, it is proven that SrO is the best one to couple with PLFO, attributed to it having the most enhanced charge separation and greatest ability to adsorb and catalyze CO2 (O2 ). This work concludes that alkaline earth metal oxide modification is feasible for the promotion of the photocatalytic activity for CO2 conversion and organic pollutant degradation.